Li1.4Al0.4Ge0.4Ti1.4(PO4)3 promising NASICON-structured glass-ceramic electrolyte for all-solid-state Li-based batteries: Unravelling the effect of diboron trioxide. Issue 3 (March 2022) - Saffirio, Sofia; Falco, Marisa; Appetecchi, Giovanni B.; Smeacetto, Federico; Gerbaldi, Claudio
Graphical abstract: Abstract: Li-ion batteries (LIBs) are the ubiquitous technology to power portable electronics; however, for the next-generation of high-performing electrochemical energy storage systems for electric vehicles and smart grid facilities, breakthroughs are needed, particularly in the development of solid-state electrolytes, which may allow for enhanced energy density while enabling lithium metal anodes, combined with unrivalled safety and operative reliability. In this respect, here we present the successful synthesis of a glass-ceramic Li1.4 Al0.4 Ge0.4 Ti1.4 (PO4 )3 NASICON-type solid-state electrolyte (SSE) through a melt-casting technique. Being grain boundaries crucial for the total ionic conductivity of SSEs, the effect of the addition of diboron trioxide (B2 O3, 0.05 wt.%) to promote their liquefaction and restructuring is investigated, along with the effects on the resulting microstructures and ionic conductivities. By the thorough combination of structural-morphological and electrochemical techniques, we demonstrate that bulk materials show improved performance compared to their powder sintered counterpart, achieving remarkable ion mobility (> 0.1 mS cm –1 at –10 °C) and anodic oxidation stability (> 4.8 V vs Li + /Li). The addition of B2 O3 positively affects the grain cohesion and growth, thus reducing the extension of the grain boundaries (and the related grain/grain interface resistance) and, therefore, increasing the overall ion mobility. In addition, B2 O3 is seen to contrast the microcracks formation in the LAGTP system under study which, overall, shows very promising prospects as SSE for the next-generation of high-energy density, safe lithium-based batteries.